A New Flow Cytometry-Based Single Platform for Universal and Differential Serodiagnosis of HTLV-1/2 Infection - Pimenta de Paiva, Luciene; Coelho-dos-Reis, Jordana Grazziela Alves; Trindade, Bruno Caetano; Peruhype-Magalhães, Vanessa; Silva Araújo, Márcio Sobreira; Gonçalves, Juan Jonathan; Nogueira-Souza, Ana Caroline; Pereira Martins, Júlia; Lopes Ribeiro, Ágata; Starling, Ana Lucia; Alcântara, Luiz Carlos Júnior; Ribeiro, Maísa Aparecida; et al. (Frontiers in Immunology, 2022)
In the present work, we developed and evaluated the performance of a new flow cytometry-based single platform, referred to as “FC-Duplex IgG1 (HTLV-1/2)”, for universal and differential serodiagnosis of HTLV-1/2 infection. The proposed technology employs a system for detection of IgG1 antibodies in a single competitive immunofluorescence platform by flow cytometry using fluorescent-labelled stained MT-2/MoT cell line mix coupled to a high sensitivity development system (Biotin/Streptavidin/Phycoerythrin). Stability of fluorescent-labelling and antigenicity of MT-2 and MoT cell lines were confirmed upon storage at -20ºC for 2, 6 and 12 months. The anti-HTLV-1/2 IgG1 reactivity, expressed as percentage of positive fluorescent cells (PPFC) was evaluated for each target antigen along the titration curve of test serum samples (1:32 to 1: 4,096). Upon selection of target cell line and serum dilutions with higher segregation score between groups, the performance of “FIX” and “FIX & PERM” protocols were evaluated. The “FIX” protocol presented excellent performance indices (Se=92%/Sp=94%/AUC=0.96; Se=96%/Sp=100%/AUC=0.99) for the universal (HTLV-1/2 vs NI) and differential (HTLV-1 vs HTLV-2) diagnosis of HTLV-1 infection, respectively. Optimisation of “FIX” protocol using the principle of synchronous and asynchronous pairwise analysis further improved the performance of “FC-Duplex IgG1 (HTLV-1/2)”, using the “FIX” protocol for differential diagnosis of HTLV-1 and HTLV-2 infections (Se=100%/Sp=100%/AUC=1.00). In conclusion, the “FC-Duplex IgG1 (HTLV-1/2)” method represent an innovation in the biotechnology segment with potential to compose a serological kit for differential diagnosis of HTLV-1/2 infection for reference laboratories and blood centres.